Tuna condensate as a promising low-cost substrate for glutamic acid and GABA formation using Candida rugosa and Lactobacillus futsaii. (July 2018) - Sanchart, Chatthaphisuth; Watthanasakphuban, Nisit; Boonseng, Oranart; Nguyen, Thu-Ha; Haltrich, Dietmar; Maneerat, Suppasil
Graphical abstract: Highlights: This is the first report for glutaminase-producing Candida rugosa . Tuna condensate is an excellent source for natural glutamic acid and gamma-aminobutyric acid (GABA) formation. Two fermentation steps were designed to produce glutamic acid and GABA consecutively in tuna condensate. GABA productivity reached to 135 mg/L/h on a laboratory scale. This study provides a new product from tuna condensate containing high levels of GABA. Abstract: Tuna condensate is a by-product from the tuna canning industry rich in N-containing compounds that currently is still underutilized. A two-step microbial process for the conversion of glutamine from tuna condensate to gamma-aminobutyric acid (GABA) via glutamic acid was developed. This process is based on Candida rugosa 8YB and Lactobacillus futsaii CS3, which were both isolated from Kung-Som, a Thai fermented shrimp condiment. C. rugosa was selected based on its ability to almost quantitatively convert glutamine to glutamic acid in modified glutamine medium. Both strains were encapsulated in sodium alginate before they were added to tuna condensate in order to increase their viability. This two-step process, in which the two conversion steps were conducted separately, resulted a final GABA productivity of 135 mg/L/h. These results show that tuna condensate can be used as a cheap substrate for natural glutamic acid and GABA formation on an industrial scale. Moreover, this provides a new product containing high levels of GABA that could be used as a flavoring agent or in animal feed.